Reinterpretasi Konsep Ta‘Āruf dalam Al-Qur’an dan Relevansinya Terhadap Pembentukan Keluarga Sakinah di Era Digital: Studi Tafsir Quraish Shihab dan Hamka - Ubaidillah Ubaidillah; Ahmad Kamaluddin; Abd. Muid N (Riviera Publishing, 2026)
The development of digital technology has brought significant changes to patterns of social interaction, including the process of ta'āruf as the initial stage of family formation. This phenomenon requires a re-understanding of the concept of ta'āruf in the Qur'an to remain aligned with Islamic values and contemporary challenges. This research aims to reinterpret the meaning of ta'āruf in the Qur'an and analyze its relevance in building a sakinah family in the digital era through the study of Quraish Shihab's and Hamka's tafsir. This research uses a qualitative method with a library research approach and comparative analysis of the tafsir works of both mufassir, particularly in interpreting verses related to social relations and marriage. The research results show that ta'āruf is not simply understood as a formal process of getting to know each other, but as an interaction based on ethical values, moral responsibility, and the purpose of benefit. Quraish Shihab emphasizes the contextual and social aspects of ta'āruf, while Hamka highlights the moral and spiritual dimensions. This reinterpretation shows that the concept of ta'āruf in the Qur'an remains relevant for building a sakinah family in the digital era, as long as the process is carried out in accordance with sharia principles and Islamic moral values.